Forest Tree Improvement Programmes in Uttar Pradesh - Gupta, Chandra; Dwivedi, A. K.; Shivkumar, Padmini (Indian Forester, 1992)
In U. P., Tree Improvement Programme is being undertaken in the three regions of Silviculture i.e. Hills, Sal and Southern Region. This paper includes the improvement programme of Shisham being carried out in the Forest Genetics Section, F.R.L., Kanpur. The preliminary results indicate that there are advantages in Forest Tree Improvement Programmes.